Who’s afraid of Adam Smith? : - Dougherty, Peter J. (John Wiley & Sons, 2002)
In the course of his argument, Dougherty follows Adam Smith’s ideas through several generations of economic thought, from nineteenth-century economic philosophers such as Alfred Marshall, who maintained a focus on moral sentiments while extending the field’s technical reach, to twentieth-century giants such as John Maynard Keynes, Paul Samuelson, and Milton Friedman, whose analytical economics have served to defend and expand market democracy.